Recent progress using the Staudinger ligation for radiolabeling applications. (18th January 2018) - Mamat, Constantin; Gott, Matthew; Steinbach, Jörg
Abstract : The increasing application of positron emission tomography and single‐photon emission computer tomography in radiopharmacy and nuclear medicine has stimulated the development of a multitude of novel and versatile bioorthogonal conjugation techniques. Currently, there is particular interest in radiolabeling biologically active, high molecular weight compounds like peptides, proteins, or antibodies, but also for the labeling of small organic compounds. An enormous challenge in radiolabeling these biologically active molecules is that the introduction of radiohalogens like fluorine‐18 as well as various radiometals proceeds under harsh conditions, which could destroy the biomolecule. The Staudinger ligation is one of the most powerful bioorthogonal conjugation techniques. The reaction proceeds over wide temperature and pH ranges; an amide (peptide) bond is formed as the ligation unit, which minimizes distortion of the structure; no isomers are obtained; and the reaction proceeds without any metal catalyst. Due to this adaptability, this robust ligation type is a perfect candidate with a high potential for various applications in the field of radiopharmacy for the labeling of biomolecules under mild conditions. This review summarizes recent research concerning the implementation of the Staudinger ligation for radiolabeling applications. Abstract : The variants of the Staudinger ligation belong to the most important and powerful biorthogonal conjugation reactions. This review summarizes the latest findings of labeling reactions using the Staudinger ligation for radiopharmaceutical applications.